Pseudonymity and Pseudoallophony: the Onomastic Masks by Álvaro Cunqueiro in his Articles and Translations - Costas, Xosé-Henrique (Madrygal. Revista de Estudios Gallegos, 2021)
During half a century of poetic creation and collaborations in the press, Cunqueiro signed thousands of articles and translations with pseudonyms and many poetic translations with pseudoallophones, so that the onomatic masks used by the Mindoniense exceed one hundred. In this article we approch to those other masked Cunqueiro, we reveal their shapes and advance some hypotheses about the reasons that led Cunqueiro to use them. We delve into this ludic onomastic spiral of the Mindoniense revealing half a hundred poems of fantastical alophony or pseudoalophony – which could be original poems by Cunqueiro – and two more pseudonyms used as supposed “translators assistents” of German and Swedish poetry.